Analysing China’s foreign direct investment in manufacturing from a high-low manufacturing perspective - Liu, K.; Daly, K.; Varua, Maria (Elsevier BV, 2014)
Since China opened its economy to foreign investment in 1979, it has become the second largest foreign direct investment (FDI) destination in the world after the USA. Over the past three decades, the manufacturing sector has dominated China's FDI inflow, however, when manufacturing activity is bifurcated into low and high technology classes, it becomes evident that China is in a transition stage moving from FDI in traditional low-tech activity to a high-tech manufacturing environment. This paper attempts to analyse the key determinants of FDI inflow across low and high technology manufacturing industry across four geographical regions of China. In the paper we empirically investigate the determinants of FDI high–low tech inflow by market size, labour cost, labour quality, and government spending on human capita.